Technopreneurship dalam Perspektif Pendidikan Kewirausahaan dan Pengembangan SDM Unggul - Ahmad Junaidi; Muhamad Yusuf; Samsudin; Elfa Setiawan; Imam Susanto; Sunarmin (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the role of technopreneurship from the perspectives of entrepreneurship education and the development of high-quality human resources (HR) in the digital era. The study employed a qualitative approach using a literature review method through descriptive analysis of relevant scientific articles. Data were obtained from Google Scholar and other credible sources published between 1964 and 2026. Of the 50 identified articles, 39 were selected through inclusion and exclusion criteria and used as the basis for analysis. The data analysis technique applied was descriptive qualitative analysis by organizing, categorizing, and systematically interpreting the findings. The results indicate that technopreneurship plays a strategic role in encouraging innovation, improving business efficiency, and expanding economic access, particularly in the MSME sector. Technology-based entrepreneurship education has proven to be an important factor in developing adaptive and innovative technopreneur competencies. Case studies of Gojek, Tokopedia, and Shopee demonstrate that the utilization of digital technology can create significant economic and social value. However, the development of technopreneurship still faces challenges, including low digital literacy, limited infrastructure, and gaps between education and industry needs. This study emphasizes the importance of strengthening curricula, developing innovation ecosystems, and improving HR capacity as strategic steps to support the sustainability of technopreneurship